Ledipasvir and sofosbuvir for 12 weeks for hepatitis C virus genotype 2 infection: A propensity score matched analysis. Issue 2 (19th November 2019) - Ogawa, Eiichi; Nomura, Hideyuki; Nakamuta, Makoto; Kawano, Akira; Dohmen, Kazufumi; Kajiwara, Eiji; Satoh, Takeaki; Koyanagi, Toshimasa; Takahashi, Kazuhiro; Ooho, Aritsune; Azuma, Koichi; Furusyo, Norihiro; et al.
Abstract : Aim: Hepatitis C virus genotype 2 is common in East Asia, sub‐Saharan Africa, and Latin America. However, many countries in these areas lag behind other areas of the world in government approval for new direct‐acting antivirals. The aim of this study was to evaluate the treatment outcome of ledipasvir/sofosbuvir (LDV/SOF) for patients with chronic hepatitis C virus genotype 2 infection. Methods: This is a two‐part multicenter, real‐world cohort study. Study 1 consisted of 58 consecutive patients who were treated with LDV/SOF for 12 weeks. Study 2 used propensity score matching for LDV/SOF ( n  = 58) and glecaprevir/pibrentasvir ( n  = 207) treatment groups (1:1) with a set of clinically important variables. Sustained viral response 12 weeks after the end of treatment (SVR12) and adverse events were evaluated in both studies. Results: In study 1, the overall SVR12 rates of the intention‐to‐treat and modified intention‐to‐treat populations were 94.8% (55/58) and 96.5% (55/57), respectively. High SVR12 rates were observed in almost all subgroups, including older age, compensated cirrhosis, and treatment experience. In study 2, propensity score matching of the entire study population yielded 52 matched pairs with similar baseline characteristics. There were no statistically significant differences between the LDV/SOF (96.1%) and glecaprevir/pibrentasvir (98.0%) groups in the overall SVR12 rates of the modified intention‐to‐treat populations, and their rates of treatment discontinuation and adverse events were similar. Conclusions: Treatment with LDV/SOF for hepatitis C virus genotype 2 resulted in a high rate of SVR12 and excellent tolerability. The outcomes of LDV/SOF were very similar to those of glecaprevir/pibrentasvir.